(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Methanol is an alternate fuel that is renewable, technologically and commercially appealing and one of the most advantageous fuels over conventional fossil fuels. Methanol was recently used to satisfy certain environmental and economic issues, as an option to conventional fuels for internal combustion (IC) engines. In this study we have discussed about the methanol, methods of using methanol as an engine fuel, uses of methanol fuel in internal combustion engine, which is concluded that the Developing and applying methanol in order to substitute existing fossil fuel fuels will eliminate conventional emissions regulation requirements and economic costs.